EPIDEMIOLOGY OF ANEMIA IN GEZIRA STATE, SUDAN: INSIGHTS FROM TYPE 2 DIABETES PATIENTS - Ahmed, Hassan Ali; Mohamed, Fatima Abdelrahman (Global Journal of Medical and Health Science, 2023)
Background: Anemia is a common complication of diabetes mellitus, significantly impacting the overall health and survival of diabetic patients. Globally, the co-occurrence of anemia and diabetes varies across populations. This study aimed to determine the prevalence of anemia among type II diabetic patients in Gezira State, Sudan. Methods: A cross-sectional laboratory-based study was conducted at Alkhair Medical Center, Wad Medani, Gezira State, Sudan, from March to December 2020. A total of 100 type II diabetic patients (32 males and 68 females) aged 30 to 90 years (mean age 52.26 ± 13.58 years) participated. Blood samples were collected, and RBC parameters were analyzed using Sysmex XP-300 Automated Analyzer. Data analysis was performed using SPSS (v 25.0). Results: The study found that 7% of type II diabetic patients had anemia. Among these, 85.7% had mild anemia, and 14.3% had moderate anemia based on hemoglobin levels. Morphologically, 57.14% had microcytic hypochromic anemia, 28.57% had normocytic normochromic anemia, and 14.29% had macrocytic anemia based on RBC indices. Anemia was more prevalent in females (7.35%) than males (6.25%). Patients aged 30-40 years and those with diabetes duration of less than 5 years had a higher prevalence of anemia. Discussion: The study revealed a 7% prevalence of anemia among type II diabetic patients in Gezira State, Sudan, with most cases being mild and microcytic hypochromic. This prevalence is lower than in various international studies, possibly due to geographic, ethnic, and demographic differences. The findings emphasize the importance of addressing anemia in diabetic patients to improve their overall health and reduce the risk of complications